FRI0522 OPIOIDS PRESCRIPTION AT DISCHARGE IN HOSPITALIZED PATIENTS: AN ANALYSIS FROM A RHEUMATOLOGY WARD OF A SWISS TERTIARY HOSPITAL. (13th June 2020) - Dumusc, A.; Valerio, F.; Hügle, T.
Abstract : Background: Opioids prescription for non-cancer pain has come under intense scrutiny as opioids abuse has become a major public health issue. Chronic opioid use is common among patients with rheumatic diseases. There are data showing that opioids are associated with a higher mortality in osteoarthritis patients receiving joint replacement. However, more data are needed on opioids use and prescription in rheumatology inpatients [1]. Objectives: To evaluate inpatient characteristics on opioid prescription at discharge from our rheumatology ward in 2017 and 2019. Methods: We prospectively recorded analgesics prescription patterns of paracetamol, nonsteroidal anti-inflammatory drugs (NSAIDs), weak opioids (tramadol/codeine) and strong opioids at discharge for all patients hospitalized in the Rheumatology Department from May to October 2017 and from October to December 2019. Statistical analyses consisted of descriptive statistics and univariate/multivariate logistic regression. P≤0.05 was considered statistically significant. Results: We analysed 240 hospital inpatient stays of 223 patients (mean age 64 years). At discharge, 25% of patients were respectively on weak opioids (tramadol/codeine) and 23% were on strong opioids, at a fixed dosage. Overall, a minority of patients were on opioids monotherapy (20% for weak opioids and 22% for strong opioids), the majority receiving combined treatments with WHO class I analgesics. The highest rate of opioids prescription at discharge was observed in patients hospitalized for severe low back pain (40%) and osteoporotic fracture (30%). At discharge, all patients transferred to a nursing home and 35% of patients transferred to a transitional care unit were on opioids compared to only 16% of the patients discharged home. The majority of patients being on opioids when transferred to a transitional care unit were prescribed opioids when discharged home (86%). Opioids prescription at discharge was negatively associated with home discharge in multivariate analysis (0.23, 0.09 to 0.55, adjusted OR, 95%CI), Table 1. There was no significant association between inpatient stay length and opioids prescription at discharge. Between 2017 and 2019, we observed a non-significant decrease in opioids prescription at discharge (absolute difference -4.7%). Conclusion: Analysis of opioids prescription from a Swiss rheumatology service of a tertiary hospital show frequent opioids prescription at inpatients discharge, mainly for non-inflammatory disorders. Opioids prescription negatively predict home discharge. References: [1] Kim, S.C., Solomon, D.H. Towards defining the safer use of opioids in rheumatology. Nat Rev Rheumatol 16, 71–72 (2020). Disclosure of Interests: Alexandre Dumusc: None declared, Flore Valerio: None declared, Thomas Hügle Grant/research support from: Abbvie, Novartis, Consultant of: Abbvie, Pfizer, Novartis, Roche, Lilly, BMS